A Comprehensive Review on Wound Dressings Focus on Hydrogel-Based Materials - Manzo, Stella; Justh, Dessen (Journal of Green Energy and Environmental Engineering, 2024)
Bio-based aerogel is a lightweight, porous and high specific surface area nanomaterial prepared from natural biomacromolecules, which has shown great potential for application in the food field in recent years.Bio-based aerogels exhibit excellent adsorption, sustained release, and biocompatibility. In this paper, the preparation methods of bio-based aerogels, including the types of raw materials, the mechanism of the sol-gel method and the drying process were systematically reviewed. The physical and functional properties of bio-based aerogels were discussed. The applications of bio-based aerogels in food preservation mats, food freshness indication labels, nutrient delivery carriers, and fat in artificial meat substitutes were summarized. In addition, the challenges of bio-based aerogels in terms of large-scale production, food safety and consumer acceptance were discussed, and the future development of bio-based aerogels in functional food and industrial production were prospected.